Muhājarat : bar'rasī-i kūtāhī az mas'alah-'i muhājarat dar Balūchistän - Dānishvar, Rizā (Majmū'ah-'i magālah, 1978)
On the causes of the migration of Iranian Baluchis to adjoining countries, especially the Emirates and Pakistan.